1986
DOI: 10.1128/aac.30.5.743
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Legionella pneumophila multiplication within human macrophages by antimicrobial agents

Abstract: The activity of serial concentrations of different antimicrobial agents on the multiplication of Legionella pneumophila within human monocyte-derived macrophages was studied. The results led to the definition of a minimal extracellular concentration inhibiting intracellular multiplication (MIEC). According to the MIECs, the antimicrobial agents tested were classified in three groups: (i) very active (MIEC < 0.06 ,ug/ml), such as erythromycin, rifampin, and pefloxacin; (ii) active (1 ,ug/ml 2 MIEC 2 0.1 ,ug/ml)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
55
0
2

Year Published

1987
1987
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 20 publications
4
55
0
2
Order By: Relevance
“…This could be explained by the fact that gentamicin was present at the time of bacterial inoculation and therefore inhibited phagocytosis (14) or had its effect before phagocytosis occurred. Our results with gentamicin are similar to those of Bacheson et al (1), who have shown that gentamicin effectively kills cell-associated L. pneumophila 2.5 h after bacterial inoculation (28).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This could be explained by the fact that gentamicin was present at the time of bacterial inoculation and therefore inhibited phagocytosis (14) or had its effect before phagocytosis occurred. Our results with gentamicin are similar to those of Bacheson et al (1), who have shown that gentamicin effectively kills cell-associated L. pneumophila 2.5 h after bacterial inoculation (28).…”
Section: Discussionsupporting
confidence: 81%
“…This result may be related to the fact that intracellular ciprofloxacin levels are approximately 2.5 times the extracellular levels (4). Pefloxacin (28) and ofloxacin (25) have also been shown to inhibit intracellular L. pneumophila growth in similar in vitro models.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Strains of Legionella species that are naturally resistant to erythromycin in vitro have not been reported, although resistant mutants have been elicited in the laboratory (62). Erythromycin is bactericidal in vitro (64), but several investigators have demonstrated that it is only bacteriostatic in cultured monocytes (140,260). For these reasons and because of the severe phlebitis that accompanies intravenous administration of erythromycin, the search for alternative therapeutic agents has continued.…”
Section: Pathology and Complicationsmentioning
confidence: 99%
“…Cure Assay of antimicrobial agents in cultured macrophages may be a less costly substitute for whole animal models (140,260), but more experience with this system is needed. It will be difficult to assess the capability of antibiotics that are rapidly bactericidal to extracellular bacteria.…”
Section: Pathology and Complicationsmentioning
confidence: 99%